Evaluation of telepharmacy and the use of a gravimetric technology–assisted workflow system for remote sterile product pharmacist checks. - Jean, Stephanie J; Francart, Suzanne J; Eckel, Stephen F; Schenkat, Daniel; Eberwein, Samuel; Lamm, Matthew; Barnes, Nathan; Valgus, John M; Amerine, Lindsey B (American Journal of Health-System Pharmacy, 2020)
Purpose To evaluate the impact of remote sterile product pharmacist checks when used with a gravimetric-based technology-assisted workflow (TAWF) system on product checking accuracy, pharmacist review time, workload sharing, cost savings, and staff perceptions. Methods A double-arm, prospective study was conducted at 4 pharmacy locations for a 90-day period. Each compounded sterile product (CSP) checked by a remote pharmacist was also checked by a local pharmacist at the site of CSP preparation. An anonymous, online survey was emailed to staff before and after implementation to evaluate perceptions of the accuracy, timeliness, safety, potential impact, and value of the remote process. Results There was no statistically significant difference in the numbers of errors detected through the remote process and through the current, nonremote process (P = 0.177). The median pharmacist review time in the local process was significantly lower (P < 0.001). Remote pharmacists in the study workflow verified 30.4% of the total number of CSPs verified in the 90-day period. Annualized cost savings were calculated to be $23,770.08. Percent agreement increased from the preimplementation to the postimplementation period for survey questions about the safety of the remote process, opportunity for workload sharing, and optimization of current workflow. Percent agreement decreased for questions about the accuracy, timeliness, and value of the remote process and its impact on job security. Conclusion The study demonstrated that with use of a gravimetric-based TAWF system, there was no difference in the accuracy and safety of sterile product pharmacist checks performed remotely and those performed at the product preparation site. In addition, the remote process allows for opportunities for workload sharing and cost savings.